Sosialisasi Dan Pemanfaatan Internet Guna Menarik Peluang Usaha Dimasa Pandemic Covid-19 Kepada Masyarakat Jombang Kramat - Hermawan; Aldianur Muhammad Herjendi; Bimas Febriana Putra; Danang Prasetio Adi; Fajar Budiman; Galih Ilham Setiaji; Putra Agustiansyah; Rizza Nurul Hidayat; Seno Ariadi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The definition of Marketing is a system for carrying out marketing activities as a whole starting from product planning, pricing, promotion to designing product distribution strategies to satisfy consumers. Today, we must often hear the word Internet and we tend to be more familiar with terms such as E-Commerce, E-government and others. The letter "E" here refers to the word "Electronic", but is more widely used in the context of the internet. The goal is to introduce the use of the internet to the people of Jombang Kramat & provide an overview of useful and profitable applications for the people of Jombang Kramat. We hope that the knowledge we convey can be utilized as well as possible.